2014
DOI: 10.1016/j.neuropsychologia.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Partial maintenance of auditory-based cognitive training benefits in older adults

Abstract: The potential for short-term training to improve cognitive and sensory function in older adults has captured the public’s interest. Initial results have been promising. For example, eight weeks of auditory-based cognitive training decreases peak latencies and peak variability in neural responses to speech presented in a background of noise and instills gains in speed of processing, speech-in-noise recognition, and short-term memory in older adults. But while previous studies have demonstrated short-term plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 77 publications
2
37
1
2
Order By: Relevance
“…109 Research in older adults has demonstrated that there is evidence of at least short-term plasticity following a similar auditory-based cognitive training protocol, but that speech-in-noise and memory gains were not maintained 6 months later. 110 There are also auditory training programs that address specific auditory processing skills that have been used in adults with auditory processing disorders, such as Listening and Communication Enhancement and the Auditory Rehabilitation for Interaural Symmetry. 111,112 Environmental modifications for individuals with mTBI from an auditory perspective would focus on improving access to and clarity of sound, better signal-to-noise ratio, and ways to increase an individual's ability to listen and learn from auditory signals.…”
Section: Management Of Auditory Processing Problemsmentioning
confidence: 99%
“…109 Research in older adults has demonstrated that there is evidence of at least short-term plasticity following a similar auditory-based cognitive training protocol, but that speech-in-noise and memory gains were not maintained 6 months later. 110 There are also auditory training programs that address specific auditory processing skills that have been used in adults with auditory processing disorders, such as Listening and Communication Enhancement and the Auditory Rehabilitation for Interaural Symmetry. 111,112 Environmental modifications for individuals with mTBI from an auditory perspective would focus on improving access to and clarity of sound, better signal-to-noise ratio, and ways to increase an individual's ability to listen and learn from auditory signals.…”
Section: Management Of Auditory Processing Problemsmentioning
confidence: 99%
“…Neuropsychology is considered as a sub-discipline and specialisation area of general psychology (Anderson, Northam & Wrennall, 2014) with applications and utilisation in various fields (Postal, 2014). Although within the South African context, neuropsychology was initially considered a specialisation area (HPCSA PBP, 1999), it has recently been positioned as a separate scope of practice (HPCSA, 2011) with overlap and application in various fields.…”
Section: Scopementioning
confidence: 99%
“…Several studies with different populations have shown that FAT induces neuroplasticity, i.e., the increase in the number or strength of neuronal synapses and/or synchrony, which is evidenced by an increase of amplitude and/or a reduction of latency in the AEP [7]- [17], resulting in behavioral changes [17]- [24]. Given the above, the aim of the present study was to determine the effects of a FAT program on individuals with TBI by means of behavioral and electrophysiological tests.…”
Section: Introductionmentioning
confidence: 99%